SIMULASI BANTUAN ZAKAT OLEH PENOLONG AMIL INSTITUSI PENGAJIAN TINGGI DI SELANGOR: SIMULATION OF ZAKAT ASSISTANCE BY AMIL ASSISTANTS OF HIGHER EDUCATION INSTITUTIONS IN SELANGOR - Md Ismail, Mohammad Noorazlan; Ali, Nor Aini (Online Journal of Islamic Management and Finance (OJIMF), 2022)
The appointment of higher education institutions (IPT) as amil assistants of the Selangor Zakat Board (LZS) has been implemented since 1998. This appointment allows IPTs to collect zakat from payers and distribute it to their university staff, especially students. Eligible students will receive zakat assistance to cover part of their study costs. Accordingly, this study tries to simulate zakat assistance by IPT to students in detail. In this study, documentation method was used to collect study data. Universiti Kebangsaan Malaysia (UKM) and Universiti Putra Malaysia (UPM) were selected as the study sample. The simulation was developed using PTPTN loan rate data which is the main source of financing for student education in Malaysia. This study uses the tuition and accommodation fee structure from the official websites of UKM and UPM. As for zakat assistance, the study refers to the assistance scheme displayed through the IPT’s official zakat website and from the findings of interviews with IPT zakat representatives. Then, the data were analyzed using descriptive analysis method. The results of the study show that the simulation of zakat assistance increases students’ finances in covering the cost of education and living expenses incurred by students but still does not reach the minimum amount of expenditure required by students’ needs. From this simulation, zakat institutions and IPTs should review the rate of educational zakat assistance to students’ needs in order to achieve the minimum expenditure required throughout the study.